One Number One Citizen in Indonesia: Solution for Problematic in Court Execution Issues - Hassanain Haykal; Theo Negoro (Dialogia Iuridica, 2022)
Implementation of executions in civil cases in the Indonesian still leaves legal problems, one of which is in the event that the Execution Applicant that is not aware of the assets that are used as collateral upon the execution request on the condition that the Execution Respondent does not implement the court judgment that has permanent legal force (inkcracht van gewisjde). Despite the importance of the fulfilment of the right of the Execution Applicant as well as an inseparable part of the implementation of the State of Law. The study aims to examine the new concept of One Number One Citizen as an instrument to fulfil the rights. The study wields a normative juridical method with a conceptual approach. The result obtained that the One Number One Citizen concept was inspired by the Social Security Number policy of the United States, where every citizen has an integrated Population Identification Number managed by the Ministry of General Affairs that includes, among others: Personal Data, Transactions, Assets, Insurance, Police Records, whole community activities, varying from identification number, activities such as:  tax, banking transaction, motorized vehicles, property registration, and so on, that could be implemented through the Execution Respondent for the execution confiscation could be carried out. The recommendations that could be given are Reform of the Civil Procedure Code and the establishment of a recent situation specifically under the government of the Ministry of General Affairs that is associated with the Supreme Court upon the arrangement of the One Number One Citizen.